Social Media Portals as a Modern Form of Social Communication: An Exemplification of Polish Mediasphere - Kinal, Jaroslaw; Skora, Michal (European Scientific Journal, ESJ, 2017)
Today, internet plays an indisputable role as a means of communication, information flow, and as a point of meeting the needs of a growing number of people. The authors noted more and more important role that mass communication plays in social media. This article presents various definitions of the phenomenon and the proposed typology, and threats which entails using either incompetent social media today. This article is intended to facilitate the communication process for researchers, sociologists, media experts, and people interested in the study of the phenomenon of online communication.